Exploring the antidiabetic effect of lupenone in rats with type 1 diabetes and its underlying mechanism based on network pharmacology - Wu, Hongmei; Huang, Xulong; Xu, Feng; Li, Xiaofen; Liang, Yuqing; Yang, Liubo; Wang, Xiangpei (Penerbit Universiti Kebangsaan Malaysia, 2023)
Lupenone has been reported to possess numerous medicinal values and gives a positive antidiabetic effect. But the mechanism of preventing and treating type 1 diabetes has not been elucidated in type 1 diabetic rats. This study investigated the effects and mechanism of action of lupenone in preventing and treating type 1 diabetes by network pharmacology and diabetic rats. The blood glucose, glycosylated hemoglobin (HbA1c), insulin, and inflammatory factors in the pancreas of rats with type 1 diabetes were measured, and histopathological changes were observed after treatment with lupenone. The pharmacological network of ‘component-target-disease’ was constructed on diabetic rats. Gene function enrichment, the Kyoto Encyclopedia of Genes and Genomes pathway analysis, and molecular docking were performed. The results showed that lupenone can decrease fasting blood glucose and HbA1c levels, increase insulin content and interleukin (IL)-4, IL-10, and decrease IL-6, transforming growth factor β and tumor necrosis factor α levels in the pancreas. Furthermore, ten targets were identified, and 50 signal pathways closely related to type 1 diabetes and inflammation were screened by network pharmacology, including insulin resistance, type II diabetes, type I diabetes, insulin signal pathway, mitogen activated protein kinase (MAPK) signal pathway, and tumor necrosis factor (TNF) signal pathway. The docking affinity of potential targets and lupenone were between -3.3 and -9.8, among which caspase-3 (CASP3), cyclin-dependent kinase 4 (CDK4), inhibitor of kappaB kinase beta (IKBKB), transforming growth factor beta-1 (TGFB1), and TNF had high binding abilities. Thus, lupenone has the potential to be developed as a new drug for treating type 1 diabetes.